THE LAW APPROVING TREATIES (“UU PENGESAHAN”): WHAT DOES IT SIGNIFY? - Agusman, Damos Dumoli (Fakultas Hukum Universitas Padjadjaran, 2016)
ABSTRACTThe provisions in Article 11 of the Constitution of 1945 and Laws of the International Treaties generally requires the